Implementation of Social Media as an Effort to Improve T-Shirt Product Purchase Decisions at Adiva Digital Printing - Nadhila Putri; Netti Nurlenawati; Dexi triadinda (International Journal of Economics and Management Research, 2024)
This study aims to analyze how social media marketing strategies influence consumer purchasing decisions at Adiva Digital Printing. The research was motivated by the increasing role of digital platforms in shaping consumer behavior, particularly in the competitive MSME sector. A qualitative research approach was applied, involving in-depth interviews with key informants, direct observation of marketing activities, and documentation analysis. The findings reveal that social media platforms such as Facebook, Instagram, and WhatsApp significantly contribute to influencing purchasing decisions. Key factors include ease of access to information, detailed and attractive product descriptions, and active interactions between the business and consumers, which foster engagement and trust. Despite these positive aspects, the current marketing strategy is not yet fully optimized, as reflected by a conversion rate of only 30%. A SWOT analysis was conducted to identify internal and external factors, highlighting strengths in product quality and competitive pricing, while weaknesses were found in limited promotional efforts and low content variation. Opportunities exist in the growing use of social media among consumers, while threats include strong competition from similar businesses. This study concludes that optimizing social media marketing strategies—such as leveraging advanced features, improving responsiveness, and producing creative, engaging content—can significantly enhance customer loyalty and drive higher sales conversions. These improvements are essential for supporting sustainable growth in the MSME sector. Furthermore, this research is expected to serve as a practical reference for other MSMEs seeking to utilize social media effectively as a strategic marketing tool.